Observation of Molybdenum Emission from Impurity-Induced Long-Lived m=1 Mode on the Experimental Advanced Superconducting Tokamak - 沈永才 吕波 王福地 石跃江 吴斌 李颖颖 符佳 万宝年 (Chinese physics letters, 2016)
We observe the spectra of molybdenum for the first time since the first wall of our experimental advanced superconducting tokamak （EAST） was changed mainly to molybdenum tiles. A large amount of molybdenum accumulated in the central plasma where the long-lived m = 1 mode instability bursts is shown. Molybdenum is proved to be the main impurity species observed during the formation and lifetime of impurity-induced long-lived m= 1 mode. This may indicate that a close relationship exists between the high-Z impurity accumulation and the occurrence of long-lived m = 1 mode in EAST plasmas.